Brand Dispute Case at GoTo Company - Alessandro Christian Max; Gunardi Lie; Moody Rizqy Syailendra Putra (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
This study aims to analyze the GoTo company's brand dispute resolution arrangements, which managed to escape a lawsuit of Rp. 2 trillion related to a brand dispute filed by PT Terbit Financial Technology on November 2, 2021. Trademark rights are special (exclusive) matters. The special rights consist of the right to use and the right to give permission to other people to use the trademark rights. If a person or other party uses the special rights without the permission of the brand owner, then there has been a violation of the trademark rights. If there is a violation of trademark rights, of course there will be laws that can provide sanctions or penalties for violators. In this GoTo case, GoTo was sued by PT Terbit Financial Technology because it was accused of violating brand rights or committing plagiarism. Of course, this has caused many parties to suffer losses, both from the company's and users' side, because GoTo is a company that is quite large and has an impact in Indonesia. Law No. 15 of 2001 concerning Mark is one of the legal remedies that can resolve and become a way out of trademark dispute cases like this. The content of the lawsuit is principally in the form of a claim for compensation and/or termination of all actions related to the use of the mark.